Pendampingan Pencatatan Laporan Keuangan Berbasis Sak Emkm Pada Umkm Di Kelurahan Sidomulyo Kecamatan Stabat - Atikah Zuhra Sitorus; Nur Aliah (Jurnal Dehasen Untuk Negeri, 2026)
Micro, Small, and Medium Enterprises play an important role in the Indonesian economy, but the majority of business actors still face obstacles in financial management, particularly in recording and reporting finances in accordance with standards. This community service activity aims to improve the understanding and skills of Micro, Small, and Medium Enterprises in the Stabat District in preparing financial reports based on the Financial Accounting Standards for Micro, Small, and Medium Enterprises or SAK EMKM. The method used is a participatory approach through interactive lectures, discussions, and workshops with evaluation instruments in the form of questionnaires before and after the activity. The activity was attended by business actors in the food and trade sectors. The results of the activity showed a significant increase in understanding, with the majority of participants understanding the basic concepts of SAK EMKM and being able to compile simple financial reports. The provision of training modules containing sample financial report formats can help participants as a practical guide. This activity succeeded in increasing the financial literacy of business actors as a first step in building awareness of the importance of orderly, transparent, and accountable financial management